Pemberdayaan Masyarakat Desa melalui Ekonomi Digital untuk Peningkatan Kualitas Hidup dan Kesejahteraan Ekonomi Masyarakat Desa Bandar Jaya Kecamatan Sosoh Buay Rayap Kabupaten Ogan Komering Ulu Sumatera Selatan - Dyah Ayu Putriani; Mardiah Kenamon; RR Dimas Veronica Priharti; Dahlia; M. Apriliansyah Ramadhani; M. Agus Kurniawan; Rosmala Dewi (Rumah Jurnal PT Citra Air Nusantara, 2026)
The development of digital technology has brought significant changes to various aspects of life, including the economic activities of rural communities. However, limited digital literacy, technological access, and the ability to utilize digital platforms remain major challenges for rural communities. This community service activity aims to empower the people of Lubuk Leban Village through the implementation of the digital economy to improve their quality of life and economic well-being. Implementation methods include outreach, digital literacy training, mentoring in the use of digital media for productive businesses, and activity evaluation. The results of the activity indicate an increase in community understanding of the digital economy, the ability to utilize social media and marketplaces for marketing local products, and increased motivation to become entrepreneurs. This program is expected to become a model for sustainable digital economy-based village community empowerment.